2017
DOI: 10.1089/cbr.2016.2156
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Long Noncoding RNA Urothelial Cancer Associated 1 Promotes Cisplatin Resistance in Cervical Cancer

Abstract: Cisplatin resistance is still one of the main reasons for failure of clinical therapy for cervical cancer. But the underlying molecular mechanisms involved in cisplatin resistance of cervical cancer have still remained unclear. Recent studies reported that long noncoding RNAs (lncRNAs) are novel nonprotein-coding transcripts, which might play a key role in cancer biogenesis and prognosis. One of the lncRNAs, urothelial cancer associated 1 (UCA1), has been shown to promote different types of cancer cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…It is worthy to note that 11 lncRNAs (LNC_000231, LNC_000226, ENST00000630242.2, ENST00000426585.5, ENST00000426185.1, ENST00000471754, ENST00000518880.1, ENST00000429269.1, ENST00000562869.1, ENST00000566942.1, and ENST00000549830.2) participated in at least one pathway related to cancer, and some lncRNAs may also be involved in immune system, signal transduction, and cellular community, including adherens junction ( Figure 4 ), all of which may play a role in the tumorigenesis and progression of cancer. Although lncRNA ENST00000454467.5 has not been enriched in the pathway related to cancer, it was significantly enriched in the pathway involved in platinum drug resistance that is related to cervical cancer cell proliferation and apoptosis ( Wang et al, 2017 ). The remaining seven lncRNAs (ENST00000482019.1, ENST00000421735.1, LNC_000188, ENST00000397381.4, ENST00000539009.1, ENST00000566260.1, and ENST00000553843.5) possibly interacted with mRNAs in the KEGG pathways, including Huntington’s disease, Alzheimer’s disease, ribosome, oxidative phosphorylation, and metabolic pathways, and these pathways did not seem to be implicated in cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worthy to note that 11 lncRNAs (LNC_000231, LNC_000226, ENST00000630242.2, ENST00000426585.5, ENST00000426185.1, ENST00000471754, ENST00000518880.1, ENST00000429269.1, ENST00000562869.1, ENST00000566942.1, and ENST00000549830.2) participated in at least one pathway related to cancer, and some lncRNAs may also be involved in immune system, signal transduction, and cellular community, including adherens junction ( Figure 4 ), all of which may play a role in the tumorigenesis and progression of cancer. Although lncRNA ENST00000454467.5 has not been enriched in the pathway related to cancer, it was significantly enriched in the pathway involved in platinum drug resistance that is related to cervical cancer cell proliferation and apoptosis ( Wang et al, 2017 ). The remaining seven lncRNAs (ENST00000482019.1, ENST00000421735.1, LNC_000188, ENST00000397381.4, ENST00000539009.1, ENST00000566260.1, and ENST00000553843.5) possibly interacted with mRNAs in the KEGG pathways, including Huntington’s disease, Alzheimer’s disease, ribosome, oxidative phosphorylation, and metabolic pathways, and these pathways did not seem to be implicated in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, GO analysis suggested that six lncRNAs were enriched in the GO term named viral transcription, except for lncRNA ENST00000482019.1, which may be involved in cell adhesion and signal transduction according to the GO analysis (Supplementary Table S3 ). Moreover, a previous study suggested that lncRNA UCA1 (ENST00000397381.4) could play an important role in the pathogenesis of cervical cancer ( Wang et al, 2017 ). Therefore, 19 DE lncRNAs could play different roles in the tumorigenesis and development of cervical cancer, and they might even function as tumor suppressors or oncogenes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UCA1 has also been implicated in cervical cancer, where its overexpression promotes resistance of cervical cancer cells to cisplatin [111]. Interestingly, since CUDR is not easily detected in normal tissues and has a low level of baseline expression in comparison with other biomarkers of cancer such as CEA, it might be an effective biomarker to identify the development of cancer and cancer therapeutic responses.…”
Section: Lncrnas With a Role In Several Cancers Of The Female Reprodumentioning
confidence: 99%
“…Previous studies showed that lncRNAs are critical factors in cisplatin-resistant cervical cancer cells. 20,21 Therefore, miR503HG is likely a downstream effector of cisplatin. In view of our observation that miR503HG is downregulated in CSCC patients who received cisplatin treatment overexpression of miR503HG may serve as a target to improve cisplatin sensitivity.…”
Section: Discussionmentioning
confidence: 99%